Neonatal Asphyxia Risk in Cesarean Birth among National Health Insurance Beneficiaries: A Cross-Sectional Analysis - Udu, Waode Sitti Asfiah; Saimin, Juminten; Purnamasari, Nur Indah; Hamud, Muhammad Dzakwan (Indonesian Journal of Obstetrics and Gynecology, 2025)
Only english abstract for Indonesian Journal of Obstetrics and Gynecology (INAJOG). Abstract concise description of the background, purpose, methods, results and conclusions required. No more than 250 words. Abstract is written using Arial 8 pt. Written with the following rules: Objectives: To analyze the correlation between the time of cesarean section and the outcome of neonatal asphyxia in the National Health Insurance participants at Referral Hospitals in Kendari. Methods: This was an analytical observational study using a cross-sectional method. The population was cases of cesarean delivery in the National Health Insurance participants at Dr. Ismoyo Hospital in 2019. The total sample was 183 obtained using a simple random sampling technique. Data was collected from medical records. Data were analyzed using the Chi-Square test with a significance value of 0.05. Results: There were 47.5% cases of emergency cesarean section and 52.5% of elective cesarean section. Neonatal asphyxia occurs in 9.4% of elective cesarean sections and 6.9% in emergencies. There was no correlation between the time of cesarean section and the outcome of neonatal asphyxia (p=0.542). Conclusion: The neonatal asphyxia is not related to the time of cesarean delivery in the National Health Insurance participants. Appropriate and good treatment can reduce the risk of neonatal asphyxia. Keywords: cesarean section, elective, emergency, neonatal asphyxia